High-temperature oxidation of nuclear graphite with account of movement of the surface layer of oxidator - Komir, A.I.; Odeychuk, N.P.; Tkachenko, V.I.; Ulybkin, A.L.; Nikolaenko, A.A. (Вопросы атомной науки и техники, 2018)
At high-temperature oxidation of nuclear graphite, the oxidant flow in the near-surface region is taken into account. Macro- and microscopic modeling of the oxidation of the near-surface layer was carried out. The calculation of the diffusion coefficient of gaseous components as a function of temperature and concentration is given. The influence of the motion of the surface layer of the oxidizer on the concentration of gaseous components is studied.